Control of photorespiratory glycolate metabolism in an oxygen-resistant mutant of Chlorella sorokiniana. - Beudeker, R F (1983)
Under a gas atmosphere of 99% O2/1% CO2, wild-type cells of Chlorella sorokiniana excreted 12% of their dry weight as glycolate during photolithotrophic growth, whereas mutant cells excreted glycolate at only 3% of the cellular dry weight. The observed difference in glycolate excretion by the two cell types appears to be due to a different capacity for the metabolism of glycolate, rather than to a different glycolate formation rate. This was concluded from experiments in which the metabolism of glycolate via the glycine-serine pathway was inhibited by the addition of isoniazid. Under such conditions, glycolate excretion rates for both cell types were identical. The mutant appeared to have significantly higher specific activities of glycine decarboxylase, serine hydroxymethyltransferase, serine-glyoxylate aminotransferase, glycerate kinase, and phosphoglycolate phosphatase than did the wild type. The specific activities of D-ribulose-1,5-bisphosphate carboxylase/oxygenase, glycolate dehydrogenase, glyoxylate-aminotransferase, and hydroxypyruvate reductase were the same for wild-type and mutant cells. The internal pool sizes of ammonia and amino acids increased in wild-type cells grown under high-oxygen concentrations but were hardly affected by high oxygen tensions in the mutant cells. Our results indicate that, under the growth conditions applied, the decarboxylation of glycine becomes the rate-limiting step of the glycine-serine pathway for the wild-type cells of C. sorokiniana.